Time and Timelessness in Victorian Poetry - Huber, Irmtraud (Edinburgh University Press, 2025)
Time and Timelessness in Victorian Poetry explores the question of poetry’s relation to time and argues that this relation is historically contingent – as the concept of time changes, so too do the shaping forms and definitions of poetry. Victorian literature provides a rich testing field for its hypothesis, since the nineteenth century saw momentous changes in the ways people thought about and experienced time. This book demonstrates that these changes were an important factor for some of the long-term developments in Victorian poetry, like its loss of cultural prestige, the popularity of mixed genres like the poetic sequence, the dramatic monologue and the verse novel, and the demise of metrical poetry as the norm. Moreover, the historical perspective offered questions some widely held assumptions, not only about poetry, but also about time itself. Thus, the theoretical relevance of this study extends well beyond its Victorian context.